Characterization of hormone receptor and HER2 status in breast cancer using mass spectrometry imaging - Gonçalves, Juliana P. L.; Bollwein, Christine; Noske, Aurelia; Jacob, Anne; Jank, Paul; Loibl, Sibylle; Nekljudova, Valentina; Fasching, Peter A.; Karn, Thomas; Marmé, Frederik; Müller, Volkmar; Schem, Christian; et al. (International journal of molecular sciences, 2023)
Immunohistochemical evaluation of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor-2 status stratify the different subtypes of breast cancer and define the treatment course. Triple-negative breast cancer (TNBC), which does not register receptor overexpression, is often associated with worse patient prognosis. Mass spectrometry imaging transcribes the molecular content of tissue specimens without requiring additional tags or preliminary analysis of the samples, being therefore an excellent methodology for an unbiased determination of tissue constituents, in particular tumor markers. In this study, the proteomic content of 1191 human breast cancer samples was characterized by mass spectrometry imaging and the epithelial regions were employed to train and test machine-learning models to characterize the individual receptor status and to classify TNBC. The classification models presented yielded high accuracies for estrogen and progesterone receptors and over 95% accuracy for classification of TNBC. Analysis of the molecular features revealed that vimentin overexpression is associated with TNBC, supported by immunohistochemistry validation, revealing a new potential target for diagnosis and treatment.